2010
DOI: 10.1016/j.fertnstert.2009.06.039
|View full text |Cite
|
Sign up to set email alerts
|

The molecular signature of endometriosis-associated endometrioid ovarian cancer differs significantly from endometriosis-independent endometrioid ovarian cancer

Abstract: Objective To determine whether endometriosis-associated endometrioid cancer (EAOC) is a specific entity compared with endometrioid cancer not associated with endometriosis (OC). Design Case-control study. Setting University hospital research laboratory. Patient(s) Seven patients with endometriosis-associated ovarian cancer EAOC and five patients each with OC, ovarian endometriosis, and benign ovaries. Intervention(s) Ovarian tissue samples were collected from surgical procedures. Main Outcome Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…25 Also, endometriotic lesions and endometroid ovarian carcinoma share overexpression of a distinct set of genes (eg, SICA2, CCL14, and Cripto-1) that are not deregulated in serous carcinomas. 26 The mutational data gathered in human cancer tissue from patients with endometrioid ovarian carcinomas were confirmed in a genetic mouse model of ovarian carcinoma. Expression of oncogenic KRAS or deletion of phosphatase and tensin homolog (PTEN) gave rise to endometriosis in the mouse ovary.…”
Section: Genetic Insights Into Ovarian Carcinoma Development: Two Majmentioning
confidence: 85%
“…25 Also, endometriotic lesions and endometroid ovarian carcinoma share overexpression of a distinct set of genes (eg, SICA2, CCL14, and Cripto-1) that are not deregulated in serous carcinomas. 26 The mutational data gathered in human cancer tissue from patients with endometrioid ovarian carcinomas were confirmed in a genetic mouse model of ovarian carcinoma. Expression of oncogenic KRAS or deletion of phosphatase and tensin homolog (PTEN) gave rise to endometriosis in the mouse ovary.…”
Section: Genetic Insights Into Ovarian Carcinoma Development: Two Majmentioning
confidence: 85%
“…For example, in a study comparing ovarian and uterine endometrioid adenocarcinomas, Catasus et al [8] noted that although the ovarian tumors overall had lower frequencies of PTEN mutations and microsatellite instability, these abnormalities were more common in the ovarian tumors associated with endometriosis. Recently, Banz et al [22] reported differences in gene profiling between endometriosis-associated and endometriosis-independent EC. Previously, we showed that although only a minority of low-grade EC expressed the Wilms tumor antigen WT1, none of the positive cases were related to endometriosis [23].…”
Section: Introductionmentioning
confidence: 99%
“…For CC, a 113-gene signature that was reported to be able to differentiate between CC and high-grade serous OvCa was used ( Hughes et al , 2016) while for EC, two studies comparing EC against high-grade serous OvCa were used after identifying 15 underexpressed genes and 40 overexpressed genes in EC ( Banz et al , 2010; Uehara et al , 2015). Of the 113 CC-specific genes, 11/34 of the underexpressed genes were downregulated at the proteomic level while 40/79 overexpressed genes were upregulated at the proteomic level ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%